Case definitions integrating empiric and consensus perspectives. Issue 1 (2nd January 2016) - Jason, Leonard A.; McManimen, Stephanie; Sunnquist, Madison; Brown, Abigail; Furst, Jacob; Newton, Julia L.; Strand, Elin Bolle
Abstract : Background : There has been considerable controversy regarding how to name and define the illnesses known as myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS). The Institute of Medicine (IOM) report has proposed new clinical criteria and a new name for this illness, but aspects of these recommendations have been scrutinized by patients and scientists. Purpose : It is possible that both empiric and consensus approaches could be used to help settle some of these diagnostic challenges. Using patient samples collected in the USA, Great Britain, and Norway ( N  = 556), the current study attempted to categorize patients using more general as well as more restricted case definitions. Results : Overall, the outcomes suggest that there might be four groupings of patients, with the broadest category involving those with chronic fatigue ( N  = 62), defined by six or more months of fatigue which cannot be explained by medical or psychiatric conditions. A second category involves those patients who have chronic fatigue that can be explained by a medical or psychiatric condition ( N  = 47). A third category involves more specific criteria that have been posited both by the IOM report, Canadian Clinical Case criteria, ME-ICC criteria and a more empiric approach. These efforts have specified domains of substantial reductions of activity, post-exertional malaise, neurocognitive impairment, and sleep dysfunction ( N  = 346). Patients with these characteristics were more functionally impaired than those meeting just chronic fatigue criteria, p  < .05. Finally, those meeting even more restrictive ME criteria proposed by Ramsay, identified a smaller and even more impaired group, p  < .05. Conclusion : It is important that scientists world-wide develop consensus on how to identify and classify patients using clinical and research criteria, and ultimately develop subtypes within such categories.